L-phenylalanine in potato onion (Allium cepa var. aggregatum G. Don) root exudates mediates neighbor detection and trigger physio-morphological root responses of tomato - Yu, Hongjie; Gao, Danmei; Khashi u Rahman, Muhammad; Chen, Shaocan; Wu, Fengzhi (Frontiers in Plant Science, 2023)
Despite numerous recent insights into neighbor detection and belowground plant communication mediated by root exudates, less is known about the specificity and nature of substances within root exudates and the mechanism by which they may act belowground in root-root interactions. Here, we used a coculture experiment to study the root length density (RLD) of tomato (Solanum lycopersicum L.) grown with potato onion (Allium cepa var. aggregatum G. Don) cultivars with growth-promoting (S-potato onion) or no growth-promoting (N-potato onion) effects. Tomato plants grown with growth-promoting potato onion or its root exudates increased root distribution and length density oppositely and grew their roots away as compared to when grown with potato onion of no growth-promoting potential, its root exudates, and control (tomato monoculture/distilled water treatment). Root exudates profiling of two potato onion cultivars by UPLC-Q-TOF/MS shound that L-phenylalanine was only found in root exudates of S-potato onion. The role of L-phenylalanine was further confirmed in a box experiment in which it altered tomato root distribution and forced the roots grow away. In vitro trial revealed that tomato seedlings root exposed to L-phenylalanine changed the auxin distribution, decreased the concentration of amyloplasts in columella cells of roots, and changed the root deviation angle to grow away from the addition side. These results suggest that L-phenylalanine in S-potato onion root exudates may act as an “active compound” and trigger physio-morphological changes in neighboring tomato roots.